High-Performance Thin Layer Chromatography Determination of Olanzapine in Pharmaceutical Dosage Form - Saxena, Vinay; Zaheer, Zahid; Farooqui, Mazhar (Asian Journal of Chemistry, 2010)
A simple, selective, precise and stability-indicating high-performance thin layer chromatographic method of analysis of olanzapine in pharmaceutical dosage form was developed and validated. The method employed TLC aluminium plates precoated with silica gel 60F-254 as the stationary phase. The solvent system consisted of toluene-methanol-ethyl acetate-ammonia (8 : 2 : 1 : 0.1 v/v/v/v). This system was found to give compact spots for olanzapine (Rf value 0.25). Olanzapine was subjected to acid and alkali hydrolysis, oxidation, photochemical degradation and thermal degradation. Also, the degraded product was well separated from the pure drug. Densitometric analysis of olanzapine was carried out in the absorbance mode at 280 nm. The linear regression analysis data for the calibration plots showed good linear relationship with coefficient of regression value, r2 = 0.9991 in the concentration range 10.8–108.0 ng/spot. The value of correlation coefficient, slope and intercept were 0.9995, 22.49 and 18.06, respectively. The method was validated for precision, recovery, ruggedness and robustness. The limits of detection and quantitation were 5.4 and 10.8 ng/spot, respectively. The drug undergoes degradation under acidic, basic, photochemical degradation and thermal degradation conditions. All the peaks of degraded product were resolved from the active pharmaceutical ingredient with significantly different Rf values. The samples degraded with hydrogen peroxide showed no additional peak. This indicates that the drug is susceptible to acid-base hydrolysis degradation, photochemical degradation and thermal degradation. Statistical analysis proves that the method is reproducible and selective for the estimation of said drug. As the method could effectively separate the drug from its degradation product, it can be employed as a stability-indicating one.